2022
DOI: 10.1161/circulationaha.122.059573
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Household Salt Substitution Intervention: Findings From 20 995 Participants of the Salt Substitute and Stroke Study

Abstract: Background: : The Salt Substitute and Stroke Study (SSaSS) ─ a five-year cluster randomized controlled trial, demonstrated that replacing regular salt with a reduced-sodium added-potassium salt substitute reduced the risks of stroke, major adverse cardiovascular events and premature death among individuals with prior stroke or uncontrolled high blood pressure living in rural China. This study assessed the cost-effectiveness profile of the intervention. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 33 publications
(62 reference statements)
4
21
0
Order By: Relevance
“…6 Moreover, the Salt Substitute and Stroke Study confirmed that salt substitute in China was a cost-saving and cost-effective policy, salt reduction could reduce the risk of stroke by 14%. 7 Although sodium intake remains at a high level after implementing salt reduction campaigns in China, it decreased from 6.3 to 4.1 g/d (from 16.0 to 10.4 g/d for salt intake) during 1991 to 2015. 8 Consequently, previous study estimated the long-term trends of stroke death attributable to high sodium intake using GBD 2016 and showed a declining trend of the age-standardized mortality rates (ASMRs), the period effect, and the cohort effect from 1990 to 2016 and further confirmed that salt reduction is a low-cost and effective strategy for stroke prevention among the Chinese population.…”
mentioning
confidence: 99%
“…6 Moreover, the Salt Substitute and Stroke Study confirmed that salt substitute in China was a cost-saving and cost-effective policy, salt reduction could reduce the risk of stroke by 14%. 7 Although sodium intake remains at a high level after implementing salt reduction campaigns in China, it decreased from 6.3 to 4.1 g/d (from 16.0 to 10.4 g/d for salt intake) during 1991 to 2015. 8 Consequently, previous study estimated the long-term trends of stroke death attributable to high sodium intake using GBD 2016 and showed a declining trend of the age-standardized mortality rates (ASMRs), the period effect, and the cohort effect from 1990 to 2016 and further confirmed that salt reduction is a low-cost and effective strategy for stroke prevention among the Chinese population.…”
mentioning
confidence: 99%
“…10 In these scenarios, the potential for subsidizing the price of potassium-enriched salt to that of regular salt may be a cost-effective option for enhancing delivery. 20 SSaSS participants in intervention villages were advised to replace all regular salt with potassium-enriched salt but also to use it more sparingly than they previously used salt. The data suggest that participants were strongly adherent to the advice to switch household use of regular salt for potassium-enriched salt, reflecting the ease with which the switch can be made.…”
Section: Discussionmentioning
confidence: 99%
“…It's di cult to reduce salt intake in these countries due to the di culty of changing dietary patterns. Evidence has shown salt substitutes lower blood pressure and major adverse cardiovascular events e ciently [20]. The main challenge in both countries now is how to make the necessary adaptations to ensure the strategy of salt substitutes effectively reduces salt intake, like overcoming the extra costs of salt substitutes, which are nearly double the price of standard salt.…”
Section: Discussionmentioning
confidence: 99%